Analisis Sistem Dan Prosedur Klaim Jaminan Hari Tua (Jht) Pada Bpjs Ketenagakerjaan Cabang Medan Kota - Gilbert Herodion Sigiro; Adam Afiezan (CERED Indonesia Institute, 2022)
This study uses a qualitative research method with a descriptive approach. Qualitative descriptive is a data analysis method that explains phenomena based on things that cannot be calculated. This research requires data related to the problem that is the object of research regarding the system and procedure for Old Age Security (JHT) claims. The data obtained in the form of data from interviews with employees and participants and through related documents and direct observation. The results of this study explain that JHT claims can be made in 3 ways, both offline and online, which participants can make, namely claims by coming to the branch office, through lapak asik and through the Jamsostek Mobile (JMO) application. Of course, participants must prepare the required documents and follow the applicable procedures. Constraints that occur, sometimes participant data is invalid and participants have not mastered technology. For participants whose data is invalid, they must fill out the correction form provided by the officer so that the JHT claim can be processed. And for participants who do not understand and master technology, participants can still make claims by coming to the branch office because they will be served well by officers and participants.